2013
DOI: 10.5812/traumamon.11228
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Fracture Dislocation of the Talus: A Case Report

Abstract: IntroductionFracture - dislocations of the talus are typically due to high energy injuries. Displaced fracture - dislocations of the talus have poor outcomes in general and complications are common. Although talar fracture is common and comprises the second most common tarsal fracture, bilateral fracture - dislocations of the talus are rare. Not many reports regarding the subject can be found in the literature.Case PresentationWe report a patient with bilateral fracture - dislocations of the talus treated by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Bilateral simultaneous talar fracture dislocation is very rare and only two such reports are mentioned in the English literature 2 3. Sayegh et al 3 in 2009 described bilateral talar body fracture dislocation in a 29-year-old patient who was treated immediately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral simultaneous talar fracture dislocation is very rare and only two such reports are mentioned in the English literature 2 3. Sayegh et al 3 in 2009 described bilateral talar body fracture dislocation in a 29-year-old patient who was treated immediately.…”
Section: Discussionmentioning
confidence: 99%
“…At 28 months’ follow-up, the patient had post-traumatic arthritis on both sides with no signs of AVN. In 2013, Taraz-Jamshidi et al 2 reported a 25-year-old man with bilateral open fracture dislocation of the talus. At 2 years’ follow-up, he had developed AVN on one side.…”
Section: Discussionmentioning
confidence: 99%
“…Talar neck and body fractures are rare; they account for 0.1% of all fractures, 9 2% of all lower limb injuries, and 5% to 7% of all foot injuries. 14 Generally, fracture and dislocation of the talus usually occur as a result of high-energy injuries, 8 and they are associated with a high rate of osteonecrosis. Studies have shown that the development of osteonecrosis is more related to factors associated with the degree of initial injury, including initial displacement, comminution, and open fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of the injury involves the application of compressive stresses on the talus, which are transferred from the tibia due to the weight force exerted on it, as well as from the ground. Although talus fractures are the second- most prevalent fractures affecting the tarsal bones, the incidence of bilateral talus talus fracture-dislocation is is rare [ 2 ]. It accounts for a mere 0.06% of of dislocations and 2% of talus injuries [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hawkins described fractures occurring in the neck of the talus with their associated joint dislocations [ 3 ]. These complex injuries pose unique challenges due to the risk of complications, including avascular necrosis and post-traumatic arthritis [ 2 , 4 ]. Despite the use of suitable interventions and anatomical fixation, these injuries injuries have a poor prognosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%